Turn over Intention among Nurses: The Role of Job Demand and Job Burnout - Yulianti, Praptini (Asian Business Review, 2020)
This study aims to prove the influence of job demand on job burnout and turn over the intention. The sample of this study is 96 nurses on the hospital private sector in Surabaya, Indonesia. The sampling method uses simple random sampling with online systems. This study examines  3  hypotheses with smart PLS. The result of this study is to prove that job demand has a positive influence on job burnout, job burnout has a positive influence to turn over intention and job demand has a positive influence to turn over the intention. Practical Implications states that nurses are vulnerable to job burnout.
Keywords: Job demand; job burnout; turn over intention